(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: Pregnant and lactating women were systematically excluded from the first SARS-CoV-2 vaccine trials, leading to great uncertainty in those women and their treating clinicians concerning the safety of the SARS-CoV-2 vaccine [1]. Detailed information about the immune response in blood and breast milk of lactating women and the transmission to infants after mRNA vaccination against SARS-CoV-2 is still scarce. STUDY AIMS: We aimed to characterise the antibody responses and neutralising antibody responses against different variants of SARS-CoV-2 after mRNA vaccination in blood and breast milk of lactating women. We further aimed to compare the antibody responses to a matched cohort of non-lactating women, and to identify factors associated with antibody responses. Additionally, we assessed the occurrence of post-vaccination symptoms, health status trajectories and SARS-CoV-2 infections among participants and their infants after vaccination. METHODS: We conducted a single-centre prospective cohort study recruiting participants between October 2021 and February 2022. The study participants were recruited directly on-site at the reference vaccination centre of the Canton of Zurich, or referred to the study centre by external healthcare providers. Eligible participants were aged >18 years and had not previously been vaccinated against SARS-CoV-2 with an mRNA vaccine. The primary outcome was the antibody response (anti-S IgA, anti-S IgG, anti-N IgG) in blood plasma and breast milk in lactating women at baseline, 4 weeks and 6 weeks. Secondary outcomes were neutralising antibody responses in blood plasma at 6 weeks, as well as self-reported post-vaccination symptoms, health status (assessed using the EuroQol visual analogue scale [EQ VAS]) and SARS-CoV-2 infections in mothers and infants over the study follow-up. Antibody responses in plasma were compared with a propensity score-matched sample of non-lactating women from the population-based Zurich SARS-CoV-2 Vaccination Cohort. Descriptive statistical analyses were conducted for all outcomes, and associations between demographic and clinical factors with antibody responses were evaluated using multivariable mixed linear regression models. RESULTS: Of 45 eligible study participants, 40 lactating women completed at least two immunological assessments and were included in analyses. Study participants had a mean age of 34.9 years and 5 (12.8%, 5/39) participants reported a prior SARS-CoV-2 infection.Two weeks after the second vaccination (at 6 weeks), all study participants tested seropositive in blood plasma for anti-S IgG and anti-S IgA, with 3 (7.7%, 3/39) testing seropositive for anti-N IgG. Neutralising antibodies against the wildtype, delta and omicron variants were detected in blood plasma of 100% (40/40), 97.4% (39/40) and 64.1% (26/40) of participants, respectively. All breast milk samples tested positive for anti-S IgG, but only 15.6% (6/40) showed detectable anti-S IgA levels. Antibody responses were similar in the matched cohort of non-lactating women. Of the 136 post-vaccination symptoms reported in mothers and the 37 reported in infants (173 post-vaccination symptoms in total), the majority were reported to be of very mild to medium severity (87.1%, 108/124 in mothers; 93.5%, 29/31 in infants) and resolved spontaneously (70.7%, 70/99 in lactating women; 42.3%, 11/26 in infants). EQ VAS scores were high at baseline (median: 85, interquartile range [IQR]: 75.5–92) and showed a minimal decrease at weeks 4 and 6 (medians: 82 and 81), with self-reported wellbeing returning to baseline levels by month 6. Over six months, 52% of the study participants reached for full follow-up (13/25) reported an infection with SARS-CoV-2, all of mild severity. CONCLUSIONS: Antibody responses against SARS-CoV-2 in blood plasma and breast milk were found to be anti-S IgG-dominant, and neutralisation assays at 6 months showed high neutralisation capacity for the wildtype and delta variants in plasma. No difference between lactating and non-lactating women was found. Self-reported post-vaccination symptoms were mostly of medium severity, and health status returned to baseline levels by 6 months after a short-term decrease around 4–6 weeks. Mild infections were reported after vaccination.